THE EFFECT OF USING GROUP INVESTIGATION MODEL ON STUDENT LEARNING OUTCOMES IN STATIC FLUID MATERIAL AT SMA NEGERI 6 NORTH GORONTALO - Mahful, Sri Mutia; Odja, Abdul Haris; Buhungo, Trisnawaty Junus (MO.RI Publishing, 2025)
This study aims to test the effect of using the Group Investigation learning model on student learning outcomes in static fluid material at SMA Negeri 6 Gorontalo Utara. This study uses a quasi-experimental method with a nonequivalent control group design . The sampling technique used is total sampling , with a population of all students of class XI IPA SMA Negeri 6 Gorontalo Utara in the 2023/2024 academic year consisting of three classes. The research sample includes class XI IPA 1 as the experimental class, class XI IPA 2 as the replication class, and class XI IPA 3 as the control class. Data collection was carried out through tests, which were then analyzed using the N-gain test, effect size, and hypothesis testing. Based on the analysis, the N-gain of the experimental and replication classes is in the high category, while the control class is in the medium category. In the experimental class, the t-count value of 7.379 is higher than the t table of 1.706; in the replication class, the t value was 6.183 and in the control class, the t value was 2.952, all of which exceeded the t table value. These results indicate that the Group Investigation model has a positive effect on student learning outcomes. Thus, H1 is rejected and H0 is accepted, indicating that the model is significant in improving student learning outcomes.